Difference in manifestation of motor abilities of footballers in two levels of competition - Jeleskovic, E.; Talovic, M.; Bajramovic, I.; Lakota, R. (Sport Science - International Scientific Journal of Kinesiology, 2015)
The purpose of this research is to determine difference of manifestation parameters of football players` motor abilities at two levels of competition. For research purposes, a sample of respondents was population represented by junior football players (U-19) 8 clubs (4 clubs- 80 football players- Quality Junior League of BiH and 4 clubs- 80 football players of Entity Junior League), total of 160 respondents. Sample of variables used in this research consisted of 12 variables of basal motor abilities. The analysis was conducted between differenes of aritmetic means at univariate level, by using univariate analysis variance (ANOVA) and discriminative differences between I and II level of competition, in the level of motor abilities at multivariate level. 64 At univariate level (central and dispersion parameters) we got information of which variables carry significant differences between groups. Results of ANOVA are pointing to differences and define variables of explosive power, agility and flexibility, which in the highest degree contribute to the differences of two levels of competition. By discriminative analysis in manifest space of motor abilities at multivariate level, we got one isolated discriminative function, which is statistically significant at level p < .01, (sig..00). These differences probably occurred as a result of application of different training technologies, and planned and programmed work on higher level of competition.